Langkah CERIA “Cegah Remaja dari Anemia” dengan Buku Saku Isi Piringku - Anik Nur Laili (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
The prevalence of anemia of adolescent girls in DIY in 2018 was 36% while the prevalence at the Yogyakarta City level reached 35.2%. The high rate of anemia among adolescents is a factor in the decrease in learning concentration which results in learning achievement. One way for students to prevent anemia is by the CERIA step "Prevent Adolescents from Anemia" with the Pocket Book of My Plate Contents. CERIA steps by providing an understanding of balanced nutrition practices implemented in class X chemistry learning. Furthermore, students get a Pocket Book of My Plate Contents which is useful for helping students in compiling food menus according to guidelines for balanced nutrition practices. The results of the CERIA step "Prevent Adolescents from Anemia" with my Plate Contents Pocket Book showed that food consumption patterns had changed, namely from 17 students who consumed food according to balanced nutrition guidelines rose to 44 students. In addition, the post-test results after taking the CERIA step showed that students with normal body conditions experienced an increase of 9.2%. Body conditions with a normal body mass index have a smaller chance of iron deficiency anemia compared to students who have a less body mass index (thin). CERIA's steps provide awareness and understanding to students about the importance of maintaining a diet so that it can prevent iron deficiency anemia. The Cheerful step can be a good start to help prevent iron deficiency anemia.